The Eurasian Core and Its Edges : Dialogues with Wang Gungwu on the History of the World - Ooi, Kee Beng (Book collections on Project MUSE., 2015)
With Chinaâ€TMs transformation into a republic after two millennia as an empire as the starting point, Ooi Kee Beng prompts renowned historian Wang Gungwu through a series of interviews to discuss China, Europe, Southeast Asia and India. What emerges is an exciting and original World History that is neither Eurocentric nor Sinocentric. If anything, it is an appreciation of the dominant role that Central Asia played in the history of most of mankind over the last several thousand years.